Faktor-faktor yang Berhubungan dengan Pemanfaatan Posbindu PTM di Kelurahan Sawahan Timur Kota Padang Tahun 2024 - Najma, Salma; Kesuma, Sari Indah; Hamdanesti, Rischa (STIKes Alifah Padang, 2024)
The coverage of tetanus toxoid immunization in pregnant women in West Sumatra in 2022 was still below the target, at 69.9%, with a goal of 90%. Among the 23 community health centers (Puskesmas) in Padang City, Dadok Tunggul Hitam Community Health Center had the lowest tetanus toxoid immunization coverage (15.72%), far below the target of 90%. The aim of this study is to identify the factors associated with the completeness of tetanus toxoid immunization in pregnant women at Dadok Tunggul Hitam Community Health Center in 2024. This is a quantitative study with an analytical approach and a cross-sectional study design. The research was conducted at Dadok Tunggul Hitam Community Health Center in Padang from March to August 2024. Data collection took place from May 13 to May 28, 2024. The population consisted of all third-trimester pregnant women, totaling 221, with a sample of 69 respondents. The sampling technique used was accidental sampling. The data were analyzed univariately in the form of frequency distribution and bivariately using the Chi-Square statistical test. The results showed that more than half of the pregnant women, 37 respondents (53.6%), had incomplete tetanus toxoid immunization. Less than half, 31 respondents (44.9%), had low knowledge. More than half, 44 respondents (63.8%), lacked family support, and less than half, 18 respondents (41.9%), perceived that healthcare workers played a minimal role. There is a significant relationship between knowledge level, family support, and the role of healthcare workers with the completeness of tetanus toxoid immunization in pregnant women at Dadok Tunggul Hitam Community Health Center in Padang in 2024.In conclusion, knowledge, family support, and the role of healthcare workers are associated with the completeness of tetanus toxoid immunization. It is hoped that healthcare providers, particularly nurses, will improve basic immunization services by providing information to pregnant women through health education sessions and distributing leaflets or posters about tetanus toxoid immunization.